Differences in the Determinants of National Reserves across G7 and Rising Power Countries - Suleymanli, Javid (International Journal of Energy Economics and Policy, 2022)
The article investigates the macroeconomic factors influencing national reserves in G7 and Rising Power countries. Factors that have been demonstrated and theoretically explained by many empirical investigations were used in the study. Two distinct panel data analyses were used with a half-century-old data collection for this aim. For each nation group, four distinct specifications have been developed. Both the System-GMM method, which is one of the dynamic panel data methodologies, and the Fixed Effects method were used to estimate the generated specifications. Robustness was applied to the coefficients produced in terms of consistency by employing other variables such as external debt crisis, population, exchange rate regime, and exchange rate crisis. As a result, it is concluded that FDI and deposit interest rates have a negative influence on national reserves in G7 countries while having a beneficial effect for Rising Power countries.